Noooooooooooooooo do it yourself
2007-01-30 07:25:39
·
answer #1
·
answered by Anonymous
·
1⤊
1⤋
to do this you are going to have to take the natural log, or ln or each function.
You want to do this because with the properties of natural logs, you can move exponents to the front of the function. ( For example: 3^x=xln3)
To take the ln of a equation, you must do so to both sides, so
5^x=4^(x+1)
becomes
ln5^x=ln4^(x+1)
now, due to the propetry that allows you to bring the exponents down in front
xln5=(x+1)ln4
expand
xln5=xln4+ln4
get all the x's on one side
xln5-xln4=ln4
pull out an x
x(ln5-ln4)=ln4
solve for x
x=ln4/(ln5-ln4)
The end!
2007-01-30 07:47:43
·
answer #2
·
answered by Liz M 1
·
0⤊
2⤋
Convert both sides to log form:
x*log 5=(x+1)*log4 then look up bse 10 logs of 4 and 5 and substitute logs into the equation:
.69897*x =.60206*(x+1)
Simplify: .69897*x = .60206*x +1*.60206
Collect terms: (.69897 -.60206)x = .60206
Therefore: .09691*x =.60206
And: x = 6.212568....
2007-01-30 08:22:43
·
answer #3
·
answered by bignose68 4
·
0⤊
2⤋
Taking log of both sides
xlog5 =(x+1)log 4 so x(log 5-log4) = log4 but log5-log4=
=log(5/4)
so x= (log4)/log(5/4)=6.2126
2007-01-30 07:32:43
·
answer #4
·
answered by santmann2002 7
·
0⤊
2⤋
5^x=4^(x+1) take the ln of both sides remembering that
ln a^b=b ln a
x ln 5=(x+1) ln 4=x ln 4 + ln 4 subtract x ln 4 from each side
x ln 5 - x ln 4=ln 4 factor out x in LHS & use ln a - ln b=ln (a/b)
x(ln 5-ln 4)= ln 4
x(ln (5/4))=ln 4 divide both sides by ln (5/4)
x=ln 5 /ln (5/4)=7.21567
2007-01-30 07:31:43
·
answer #5
·
answered by yupchagee 7
·
0⤊
2⤋
5^x=4^(x+1)
log 5^x = log 4^(x+1)
x log 5 = (x+1)log 4
x/(x+1) = log 4/log 5 = .861
x = .861(x+1) = .861x + .861
x - .861x = .861
.139x = .861
x = .861/.139 = 6.19
2007-01-30 07:35:44
·
answer #6
·
answered by ironduke8159 7
·
0⤊
2⤋
5^x=4^(x+1)
5^x = 4^x * 4
x ln 5 = x ln 4 + ln 4
x (ln 5 - ln 4) = ln 4
x = ln 4 / (ln 5 - ln 4)
x = 6.21
2007-01-30 07:30:36
·
answer #7
·
answered by G4G 1
·
1⤊
2⤋
its easy
u need the numbers on the bottom to be the same
then u can make x = x+1
2007-01-30 07:26:55
·
answer #8
·
answered by SUPERMAN 4
·
0⤊
3⤋
x log (5) = (x+1) log 4
xlog(5) - x log(4) = log(4)
x (log5 - log4) = log4
x = (log4)/(log 5 -log4)
2007-01-30 07:35:58
·
answer #9
·
answered by Naturelle 2
·
0⤊
2⤋
taking log on both sides,
xlog5=(x+1)log4
(x)/(x+1)=log4/log5
2007-01-30 07:32:30
·
answer #10
·
answered by great 2
·
0⤊
2⤋